Revitalisasi pasar tradisional dalam mewujudkan pengembangan ekonomi lokal di Kabupaten Sumenep - Rillia Aisyah Haris; Elsya Muzayyana; Irma Irawati. P. (Universitas Merdeka Malang, 2019)
The various polemics of the traditional market are often the subject of ongoing conversations. Behind all the processes of economic activity that are taking place, the problems that continue to occur today are the slum condition of the market environment, disorderly parking arrangements, and congestion that often occur making the traditional market conditions increasingly out of control. Traditional market revitalization efforts have been carried out. The aim of revitalization which is actually to fix the market becomes more organized, orderly and cleaner for the convenience of the community, but until now it has not been realized. This study uses descriptive qualitative research methods. The focus in this study refers to the role of the government in local economic development through revitalization of traditional markets including the role of the coordinator and the role of the facilitator. The results of the study indicate that the local government has acted as a coordinator and facilitator in revitalizing traditional markets but has not been able to carry out optimally. One reason is the absence of a clear and specific legal umbrella governing traditional market revitalization. Some recommendations that can be offered are: 1) The Sumenep Regency Government needs to coordinate with all stakeholders involved to identify problems while finding appropriate solutions to problems in traditional market revitalization; 2) The local government of Sumenep Regency needs to establish specific policies governing the revitalization of traditional markets so that the objective of market revitalization can be achieved optimally; 3) Carry out monitoring and evaluation of the revitalization program.DOI: https://doi.org/10.26905/pjiap.v4i2.3284